2010
DOI: 10.1002/jcb.22607
|View full text |Cite
|
Sign up to set email alerts
|

Runx2/Cbfa1, but not loss of myocardin, is required for smooth muscle cell lineage reprogramming toward osteochondrogenesis

Abstract: Vascular calcification is a major risk factor for cardiovascular morbidity and mortality. Smooth muscle cells (SMCs) may play an important role in vascular cartilaginous metaplasia and calcification via reprogramming to the osteochondrogenic state. To study whether SM lineage reprogramming and thus matrix calcification is reversible and what the necessary regulatory factors are to reverse this process, we used cells isolated from calcifying arterial medias of 4-week-old matrix Gla protein knockout mice (MGP−/−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(117 citation statements)
references
References 41 publications
3
113
1
Order By: Relevance
“…Our previous study also showed that an increased ALP expression contributes to the promotion of vascular calcification in the presence of trichostatin A (TSA), a representative histone deacetylase (HDAC) inhibitor 40) . Accordingly, in the present study, the increased ALP expression induced by 5-azadC promoted the mineralization of HASMCs, while suppression of the ALP expression inhibited the development of Pi-induced vascular calcification with or A B C lar calcification 41) . Therefore, the upregulation of SM lineage genes was not associated with the 5-aza-dCpromoted mineralization of HASMCs in the present study.…”
Section: A B 471supporting
confidence: 55%
“…Our previous study also showed that an increased ALP expression contributes to the promotion of vascular calcification in the presence of trichostatin A (TSA), a representative histone deacetylase (HDAC) inhibitor 40) . Accordingly, in the present study, the increased ALP expression induced by 5-azadC promoted the mineralization of HASMCs, while suppression of the ALP expression inhibited the development of Pi-induced vascular calcification with or A B C lar calcification 41) . Therefore, the upregulation of SM lineage genes was not associated with the 5-aza-dCpromoted mineralization of HASMCs in the present study.…”
Section: A B 471supporting
confidence: 55%
“…Given previous studies suggesting a role for Runx2 in osteochondrogenic differentiation of SMCs in vitro 34,35 and in vivo, 12,21,33 we were surprised that deletion of Runx2 in SMCs did not change the overall content of chondrocyte-like cells in the intima. Our studies show that while SMC expression of Runx2 was not required for initial chondrogenesis, it was necessary for maturation of chondrocytes to a promineralizing, hypertrophic state, leading to endochondral ossification.…”
Section: Discussionmentioning
confidence: 76%
“…This might be due to absence of Runx2 upregulation (supplementary material Fig. S3B), which was shown to be crucial for vascular smooth muscle cells to express osteochondrogenic markers (Speer et al, 2010).…”
Section: Resultsmentioning
confidence: 99%